The moral structure of war : the functional utility of the principle of discrimination - Lehrke, Dylan Lee (Irish School of Ecumenics, 2012)
This dissertation sets out to conduct a utilitarian analysis of the moral-legal principles of warfare and more specifically to uncover the functional utility of the moral principle of distinction. The dissertation is structured around the conducting of a moral genealogy. Thus, chapter one examines the conditions of life in which the moral rules of war arose. This means looking at the nature of death, violence, civilization, and war. One feature emerges as being at the core of all of these conditions - mimesis.
Keywords: Religions, Theology & Ecumenics Ph.D.; Ph.D. Trinity College Dublin.